Quaternary alloy quantum dots : toward low-threshold stimulated emission and all-solution-processed lasers in the green region - Wang, Yue (2015)
Ultra-low threshold stimulated emission is demonstrated upon both one- and two-photon pumping from quaternary alloyed Cd(1−x)ZnxSe(1−y)Sy/ZnS quantum dots (QDs) in the green region for the first time. Moreover, an all-solution-processed whispering gallery mode laser is produced by coating Cd(1−x)ZnxSe(1−y)Sy/ZnS QDs on a self-assembled hemisphere. These results represent a significant progress in green lasers and hold great potential in addressing the “green gap” challenge.